Effectiveness of Happiness Curriculum A Positive Psychology Intervention in Schools by the Government of Delhi - Devi, Sunita; Patra, Swati (JOURNAL OF INDIAN EDUCATION, 2020)
One of the fundamental goals of education focuses on the overall well-being of children. The purpose of this study was to undertake a preliminary analysis of the implementation and effectiveness of the happiness curriculum introduced by the Delhi Government in the schools from nursery to class eighth. The perspectives of the teachers, parents and students towards the happiness curriculum were studied. The sample consisted of 300 students (6th to 8th class) taken from ten schools. 60 teachers and 60 parents were also included. Qualitative data was collected via semi-structured questionnaire given to students, teachers, and parents. The questionnaire covered different aspects of the curriculum and the concept of happiness. Majority of students, teachers and parents were found to be satisfied with the Happiness Curriculum and opined that it should be continued and implemented in senior classes also.